Upaya Membentuk Karakter Percaya Diri dan Kreatif Pada Anak Usia Dini Melalui Permainan Tradisional Jamuran - Mustakimah Mustakimah; Sri Mu'amamah (Journal of Early Childhood and Character Education, 2021)
The background of this research is the importance of forming good character in early childhood with the stimulation given to traditional mushroom play activities. The method used in this study is a qualitative research method. The purpose of this study is to describe how the traditional game of mold can shape the character of early childhood. Based on the results of traditional game research, molds can form characters in early childhood, including honest characters formed by the habit of children not lying when guessed by their friends, disciplined characters are formed by habituating children to follow the rules in the game, respecting friends formed by habituating children do not choose -choose friends to be there next to him and listen to the instructions of friends in front, a confident character is formed by habituation of children giving instructions in the middle of their own, creatively formed by habituation of children mentioning names of objects or animals to imitate other friends, self-confidence and brave characters formed by habituation children advance in front of the crowd alone.